Designing STEAM Education: Fostering Relationality through Design‐Led Disruption. (11th November 2019) - MacDonald, Abbey; Wise, Kit; Tregloan, Kate; Fountain, Wendy; Wallis, Louise; Holmstrom, Neil
Abstract: A significant contention underpinning the commentary around STEM / STEAM is the evidence of discipline hierarchies, and inherent binary perspectives and/or biases that lend themselves to privileging one or more disciplines over another in an interdisciplinary education context. The current focus on increasing engagement with STEM in Australian schools provides opportunities to explore how the creative and liberal arts, and arts‐based approaches to teaching and learning are being adopted to significantly enhance teaching and learning outcomes in and for STEM education. This article examines how design for a STEAM education programme evolves and is adopted in an Australian context. Tasmania represents one of the most vibrant creative communities in Australia. At the same time it has one of the lowest levels of educational attainment. Entrenched teaching habits and disciplinary hierarchies often create significant barriers to the implementation of STEAM despite genuine goodwill and enthusiasm for STEAM among teachers and within schools. This article argues that, despite the contrasting dynamics extant in the Tasmanian educational context, it is here that some of the nation's most curious and exciting examples of STEAM teaching and learning have emerged. It offers an example of an innovative learning project and proposes the means by which these disciplinary strands have been effectively entwined.